2011
DOI: 10.1530/joe-11-0103
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin 3-mediated integrin β1 signaling is required for the proliferation of folliculostellate cells in rat anterior pituitary gland under the influence of extracellular matrix

Abstract: Folliculostellate (FS) cells in the anterior pituitary gland are believed to have multifunctional properties. Using transgenic rats that express green fluorescent protein (GFP) specifically in FS cells in the anterior pituitary gland (S100b-GFP rats), we recently revealed that FS cells in primary culture exhibited marked proliferation in the presence of laminin, an extracellular matrix (ECM) component of the basement membrane. In a process referred to as matricrine action, FS cells receive ECM as a signal thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…3A and B). Cells were treated with 100 mM MMP-9 synthetic inhibitor or an equal volume of vehicle (DMSO; control group) from 0 to 72 h. In the control group, the behavior of FS cells was similar to that reported previously (Horiguchi et al 2010(Horiguchi et al , 2011a inhibitor, FS cells did not fully flatten but did extend their cytoplasmic processes. In addition, although the motility of these cells was comparable to that of the control group, they only established sparse cellular interconnections by 72 h of culture ( Fig.…”
Section: Effect Of Mmp-9 Inhibitor On Fs Cells In Primary Culturesupporting
confidence: 63%
See 2 more Smart Citations
“…3A and B). Cells were treated with 100 mM MMP-9 synthetic inhibitor or an equal volume of vehicle (DMSO; control group) from 0 to 72 h. In the control group, the behavior of FS cells was similar to that reported previously (Horiguchi et al 2010(Horiguchi et al , 2011a inhibitor, FS cells did not fully flatten but did extend their cytoplasmic processes. In addition, although the motility of these cells was comparable to that of the control group, they only established sparse cellular interconnections by 72 h of culture ( Fig.…”
Section: Effect Of Mmp-9 Inhibitor On Fs Cells In Primary Culturesupporting
confidence: 63%
“…Previously, we discovered that FS cells formed networks in the presence of laminin, a process mediated through integrin b1 signaling (Horiguchi et al 2011a). Veeravalli et al (2010) showed that MMP-9 silencing downregulates the a-subunit and b-subunit of integrin in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their role in caveolae, Cav proteins also function in other subcellular locations of the cell such as the focal adhesion complex (10,11). As has been identified in cell types other than CM, Cav and integrin function may be cooperatively regulated (12)(13)(14)(15)(16). Various human Cav3 mutations result in loss of Cav3 function, and are associated with both hypertrophic and dilated cardiomyopathies, as well as a range of neuromuscular diseases (17)(18)(19).…”
mentioning
confidence: 99%
“…For example, RVD depends on cation influx following membrane tension during hyposmotic cell swelling as shown in astrocytes and kidney cells (Hua et al, 2010). The influx of Ca 2+ in turn triggers a series of cellular signaling events, such as activation mitogen-activated protein kinases (MAPKs) including c-Jun NH2-terminal kinase, p38 MAPK and extracellular signal-regulated protein kinase 1/2 (Horiguchi et al, 2011; Shi et al, 2011). The last kinase is known to activate TRP channels (Ebner et al, 2006; Dine et al, 2014).…”
Section: Cellular Volumementioning
confidence: 99%